(untitled) (Boca Raton, Fla., 2000)
Love Canal. Exxon Valdez. Times Beach. Sacramento River Spill. Amoco Cadiz. Seveso. Every area of the world has been affected by improper waste disposal and chemical spills. Common hazardous waste sites include abandoned warehouses, manufacturing facilities, processing plants, and landfills. These sites poison the land and contaminate groundwater and drinking water.A sequel to the bestselling Ecological Risk Assessment, Ecological Risk Assessment for Contaminated Sites focuses on how to perform ecological risk assessments for Superfund sites and locations contaminated by improper disposal of wastes, or chemical spills. It integrates the authors' extensive experience in assessing ecological risks at U.S. government sites with techniques and examples from assessments performed by others. Conducting an ecological risk assessment on a contaminated site provides the information needed to make decisions concerning site remediation. The first rule of good risk assessment is "don't do anything stupid". With the practical preparation you get from Ecological Risk Assessment for Contaminated Sites you won't.
Keywords: Ecological risk assessment,Hazardous waste sites,Đánh giá rủi ro sinh thái học,Định vị chất thải nguy hiểm; Environmental aspects,Diện mạo môi trường